Yoga Kids sebagai Stimulasi Motorik Kasar untuk Anak Usia Dini - Nur Ismawati; Nelly Agustin; Eti Salafas (Universitas Ngudi Waluyo, 2024)
Children are the nation's next generation who deserve attention. According to the World Health Organization (WHO), 5-25% of pre-school children in the world experience minor brain dysfunction, including impaired fine motor and gross motor development. Gross motor skills are movements that involve large muscles. One activity that can optimize the use of all children's senses is Yoga Kids. Yoga Kids is a creative way to provide children with exercise to regulate breathing patterns and physical activity, which can have many benefits for growth and development as well as being a fun activity for all family members. The aim of this activity is to increase children's and teachers' knowledge about the importance of Yoga Kids sports and improve their ability to concentrate on learning, as well as stimulate children's growth and development, especially in terms of gross motor skills. Community Service will be carried out in 3 stages, namely the First Stage, making preparations by collaborating with partners. Second Stage Providing counseling about the benefits of Yoga Kids, using projector media and teaching Yoga Kids sports to children in a happy atmosphere. Third Stage: Conduct an evaluation by conducting interviews with PAUD and Kindergarten teachers and students. From the results of community service, it was found that this activity was attended by 48 children and 6 teachers, and the result was an increase in children's motor development abilities after the training. During the activity, the children looked enthusiastic and eager. It is hoped that heads and teachers of PAUD and Kindergarten schools will carry out Yoga Kids activities on an ongoing basis so that children's gross motor skills improve. Abstrak Anak merupakan generasi penerus bangsa yang layak untuk mendapatkan perhatian. Berdasarkan World Health Organization (WHO) menyatakan bahwa 5-25% anak usia pra sekolah di dunia mengalami disfungsi otak minor, termasuk gangguan perkembangan motorik halus dan motorik kasar. Motorik kasar adalah Gerakan yang melibatkan otot-otot besar. Salah satu aktivitas yang dapat mengoptimalkan penggunaan seluruh indera anak adalah Yoga Kids. Yoga Kids merupakan salah satu cara yang kreatif untuk memberikan Latihan anak untuk melakukan pengaturan pola nafas dan aktivitas jasmani yang dapat memiliki banyak manfaat untuk pertumbuhan dan perkembangan serta aktivitas yang menyenangkan bagi seluruh anggota keluarga. Tujuan kegiatan ini adalah meningkatkan pengetahuan anak dan guru mengenai pentingnya olahraga Yoga Kids dan meningkatkan kemampuan dalam konsenterasi belajar, serta menstimulus tumbuah kembang anak terutama dalam hal motorik kasar. Pengabdian Masyarakat akan dilaksanakan dalam 3 tahap yaitu Tahap Pertama melakukan persiapan dengan cara melakukan kerja sama dengan mitra. Tahap Kedua Memberikan penyuluhan mengenai manfaat Yoga Kids, menggunakan media Proyektor dan mengajarkan olahraga Yoga Kids pada anak dengan suasana gembira. Tahap Ketiga Melakukan evaluasi dengan cara melakukan wawancara kepada guru dan murid PAUD dan TK. Dari hasil pengabdian Masyarakat didapatkan bahwa kegiatan ini diikuti oleh 48 anak dan 6 guru dan terjadi peningkatan kemampuan perkembangan motorik anak setelah dilakukan pelatihan. Selama kegiatan berlangsung anak-anak tampak antusias dan semangat. Diharapkan kepala dan guru sekolah PAUD dan TK untuk melaksanakan kegiatan Yoga Kids secara berkelanjutan agar kemampuan motorik kasar anak meningkat.